REGIONALNE ZRÓŻNICOWANIE EFEKTYWNOŚCI AKTYWNYCH PROGRAMÓW RYNKU PRACY W POLSCE - Reichelt, Anna (Wydział Prawa i Administracji UAM, 2007)
This paper has been written on the basis o f compulsory statistical reports prepared by Polish labour offices and presents various forms of activation of the unemployed, their efficiency and the funds spent on realisation of those activities. The effectiveness o f active labour market programmes has been going down since 2001. One o f the reasons of that situation is the difference in the structural and economic development of regions in Poland. Analyses of the differences in the effectiveness of active labour market programmes (ALMP) in Polish regions show that those differences have their origin in historic and geographic determinants. The effectiveness of ALMP in counties (powiat) depends on their location. Those near large urban agglomerations achieve better employment results upon completion of an active labour market programme than those farther from large cities or in rural areas. Areas with high demand for work and with readily available qualified human resources are more attractive to potential enterprises. To increase the effectiveness of ALMP it will be necessary to change the social and economic environment and reduce the cost o f labour, to adapt the education and professional training to the needs of the labour market, and to eliminate the differences in economic and structural development of Polish regions.
REGIONAL DIFFERENCES IN THE EFFECTIVENESS OF ACTIVE LABOUR MARKET PROGRAMMES IN POLAND